Computerized Systems and Cloud Computing with the Principles of GLP - Mahalingam Palaniandi; Amalan Stanley V. (Science and Technology - Recent Updates and Future Prospects Vol. 4, 2024)
Computers, from personal PCs to the regulatory environment, play a vital role in communications, data generation, data analysis, and secure storage. They remain vital in data management, documentation, and scientific data analysis in any GLP-compliant test facility. Computers and computerized systems are used in various areas such as Data Acquisition, Data Processing and Analysis, Laboratory Information Management Systems (LIMS), Backups and Data Security, Reporting and Documentation, Quality Control and Quality Assurance, and Electronic Archiving. This chapter explores the intricacies of achieving compliance with Good Laboratory Practice (GLP) principles when employing computerized systems and harnessing the potential of cloud computing technologies within laboratory settings. It also investigates the key challenges laboratories face in maintaining GLP compliance in the context of computerized systems and cloud technology adoption. It provides a complete overview of creative solutions and best practices for effectively addressing these difficulties. The primary aim of this chapter is to provide laboratory professionals, regulators, and stakeholders with valuable insights into navigating the complex landscape of GLP compliance in an increasingly digital and interconnected world.